AKT phosphorylates H3-threonine 45 to facilitate termination of gene transcription in response to DNA damage. Issue 9 (26th March 2015) - Lee, Jong-Hyuk; Kang, Byung-Hee; Jang, Hyonchol; Kim, Tae Wan; Choi, Jinmi; Kwak, Sojung; Han, Jungwon; Cho, Eun-Jung; Youn, Hong-Duk
Abstract: Post-translational modifications of core histones affect various cellular processes, primarily through transcription. However, their relationship with the termination of transcription has remained largely unknown. In this study, we show that DNA damage-activated AKT phosphorylates threonine 45 of core histone H3 (H3-T45). By genome-wide chromatin immunoprecipitation sequencing (ChIP-seq) analysis, H3-T45 phosphorylation was distributed throughout DNA damage-responsive gene loci, particularly immediately after the transcription termination site. H3-T45 phosphorylation pattern showed close-resemblance to that of RNA polymerase II C-terminal domain (CTD) serine 2 phosphorylation, which establishes the transcription termination signal. AKT1 was more effective than AKT2 in phosphorylating H3-T45. Blocking H3-T45 phosphorylation by inhibiting AKT or through amino acid substitution limited RNA decay downstream of mRNA cleavage sites and decreased RNA polymerase II release from chromatin. Our findings suggest that AKT-mediated phosphorylation of H3-T45 regulates the processing of the 3′ end of DNA damage-activated genes to facilitate transcriptional termination.